Comparison of some methods for Reference Evapotranspiration calculation in Shahat Area, Aljabal Alakhdar- Libya - MOMEN, Mohamed A.; ABDELATTI, Osama A. (Al-Mukhtar Journal of Sciences, 2016)
This study was conducted to compare some methods for calculating the reference evapotranspiration (ETo) with FAO Penman-Monteith (FPM)which is the recommended method by the FAO to calculate the reference evapotranspiration. Sevenmethods were chosen, three of which depend on the temperature, namely, (Blaney-Criddle BC, Hargreaves- Samani HS, Thornthwaite TW), and four depend on the radiation (radiation Rd, Priestley-Taylor -PT, Makkink MK, Turc TC). Thirty seven years of climatic data for a period of 1963 to 1999 were used from meteorological station of Shahat, Aljabal Alakhdar, Libya. The obtained results showed that the method of Blaney-Criddle was the best performance compared to the FAO Penman Monteith (FPM), where the values ​​of the root mean square error (RMSE), mean bias error (MBE), the maximum error (MAXE), and the relative errors (RE) were 0.33, 0.11, 0.66 mm/day, -0.1%, respectively,while the method of Thornthwaite was the least performance, where the values ​​of the root mean square error (RMSE), mean bias error (MBE), the maximum error (MAXE), and the relative error (RE) were 1.8, 1.69, 2.76 mm/day, -46.48% respectively. The rest of the methods ranged between these values.